Head-to-Head Comparison of 68Ga-PSMA-11 PET/CT and Multiparametric MRI for Pelvic Lymph Node Staging Prior to Radical Prostatectomy in Patients With Intermediate to High-Risk Prostate Cancer: A Meta-Analysis - Wang, Xueju; Wen, Qiang; Zhang, Haishan; Ji, Bin (Frontiers in Oncology, 2021)
Purpose: To compare the diagnostic performance of 68Ga-PSMA-PET/CT and mpMRI for pelvic lymph node staging prior to radical prostatectomy in prostate cancer (PCa) patients based on per patient data. Methods: PubMed and Embase databases were searched until October 2020 for eligible studies evaluating head-to-head comparison of 68Ga-PSMA-PET/CT and mpMRI for the detection of pelvic lymph node metastases (PLNMs) using pelvic lymph node dissection (PLND) as gold standard. The pooled sensitivity, specificity and the area under the summary receiver-operating characteristics curve (AUC) were determined for the two imaging modalities. Results: Nine studies with 633 patients were included. The pooled sensitivity, specificity and AUC for 68Ga-PSMA-PET/CT vs. mpMRI were 0.79 (95% CI: 0.45–0.94) vs. 0.53 (95% CI: 0.19–0.84), 0.87 (95% CI: 0.78–0.92) vs. 0.88 (95% CI: 0.73–0.95), and 0.90 (95% CI: 0.87–0.92) vs. 0.84 (95% CI: 0.81–0.87), respectively. There was high heterogeneity for both imaging modalities and meta-regression analysis revealed that number of patients, extracted lymph node number, prevalence of PLNMs, reference standard and PSA level were potential causes of heterogeneity. Conclusion：This meta-analysis of head-to-head comparison studies confirms that there is a trend towards a higher sensitivity and diagnostic accuracy of 68Ga-PSMA-PET/CT compared to mpMRI for the detection of PLNMs in PCa patients. Nevertheless, according to current guidelines, PLND still needs to be recommended in case of negative results from 68Ga-PSMA-PET/CT due to significant risk of malignancy.